Reliability of Measuring Lumbar Range of Motion Using Modified-Modified Schober Test in Healthy Subjects - Narjes Nabavi; Mohammad Ali Mohseni-Bandpei; Zahra Mosalla-nezhad; Mahdi Rahgozar (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: Accurate assessment of lumbar range of motion is of great value for both evaluating lumbar functions and monitoring treatment progress. The purpose of this study was to determine the intra-rater reliability of lumbar flexion and extension measurements (within-day and between-days) using the Modified Modified Schober's technique (MMST). Materials & Methods: Lumbar flexion and extension of 38 healthy subjects (12-male and 26-female), with no history of low back pain, were measured by the same examiner on three occasions. The first two measurements were taken with half an hour apart on the first occasion to assess the within-day reliability and the third measurement was taken one week later to assess the between-days reliability. Results: Within-day lumbar flexion and extension measurements using Modified Modified Schober's technique were shown to be very reliable with high Intraclass Correlation Coefficients values (0.85 for flexion and 0.73 for extension). The high values of Intraclass Correlation Coefficients (0.83 for flexion and 0.68 for extension) also indicated high reliability for between-days measurements. Conclusion: The results indicated that, the Modified Modified Schober's Technique appears to be a highly reliable method for measuring lumbar flexion and extension and can be used as a reliable tool in the assessment of lumbar range of motion and monitoring therapeutic interventions.